2009
DOI: 10.1089/apc.2008.0204
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported Sexually Transmitted Disease Symptoms and Treatment-Seeking Behaviors in China

Abstract: In recent decades, sexually transmitted diseases (STDs) have reemerged and spread as a major public health problem in China. However, little effort has been made on promoting appropriate health-seeking behaviors among people living with STDs. A randomly selected sample of market vendors in Fuzhou (N = 4510) was recruited and assessed from 2003 to 2004 to examine their choice of pharmacy versus hospital, and folk remedy versus Western medicine when having STD symptoms. Approximately 11.3% of the sample (4.0% of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 27 publications
(21 reference statements)
0
17
0
Order By: Relevance
“…The findings of this study highlighted that an effective multicomponent biomedical and behavioral intervention strategy is needed urgently, including education about appropriate health-seeking behavior, 55 the promotion of condom use through enhancing peer norms within MSM networks, 56 HIV prevention on the Internet due to China has hundreds of MSM websites, expanded testing for HIV, syphilis and HBV, actively bridging to care and treatment for HIV-infected individuals and HBV vaccination for HIVnegative individuals, along with alcohol control and harm reduction. The innovative prevention measures for HIV transmission reduction, e.g., preexposure prevention (PreP), ART for prevention, should be examined in the context of Chinese MSM.…”
Section: Et Almentioning
confidence: 99%
“…The findings of this study highlighted that an effective multicomponent biomedical and behavioral intervention strategy is needed urgently, including education about appropriate health-seeking behavior, 55 the promotion of condom use through enhancing peer norms within MSM networks, 56 HIV prevention on the Internet due to China has hundreds of MSM websites, expanded testing for HIV, syphilis and HBV, actively bridging to care and treatment for HIV-infected individuals and HBV vaccination for HIVnegative individuals, along with alcohol control and harm reduction. The innovative prevention measures for HIV transmission reduction, e.g., preexposure prevention (PreP), ART for prevention, should be examined in the context of Chinese MSM.…”
Section: Et Almentioning
confidence: 99%
“…Qualitative [29] and quantitative [30,31] studies of health-seeking behaviors among those with genitourinary symptoms reveal that many individuals do not seek care in the official standardized clinic system. Small studies of female sex workers [32 • ,33] and rural-to-urban migrants [34 • ] have shown that although many high-risk groups are interested in HIV and STI testing, uptake at designated clinic sites has been low.…”
Section: Potential Determinants Of Syphilis In Chinamentioning
confidence: 99%
“…The lack of need to make an appointment in the pharmacy, extended opening hours and the provision of a confidential service (especially for young women) [9,10] are some of the favourable factors identified by the public for promoting pharmacies as the choice of access to EC. Other factors cited include convenience and much less risk of stigma, especially for those from Asian countries [11,12] …”
Section: Pharmacists' Role In Sexual and Reproductive Health Mattersmentioning
confidence: 99%
“…Evidence shows that pharmacists can, and must, be proactive in providing STI screening, ensuring patients adhere to STI and HIV/AIDS treatments and practise safe sex [22–26] . In countries where the dispensing of antibiotics without prescription to treat STI still occurs, the public's behavioural pattern in choosing pharmacies as one of the main options for seeking treatment is worthy of further investigation [11,24,27,28] . Confirming possible underlying factors leading to this pattern of behaviour, such as perception of less risk of stigma by going to the pharmacy, lower treatment cost at the pharmacy or clearer dissemination of information by pharmacists, may reflect that necessary changes to policies and practices for these countries are required.…”
Section: Pharmacists' Role In Sexual and Reproductive Health Mattersmentioning
confidence: 99%
See 1 more Smart Citation